Dakwah dan Perubahan Sosial dalam Persfektif Teori Sosiologi - H. M. Bahri Ghozali; M. Jamil (Mau'idhoh Hasanah, 2019)
Abstract Da'wah not only conveys religious messages, but it also organizes social life. For this reason, da'wah is faced with the performance of theoretical analysis that deals directly with social theories. One theory that helps the performance of da'wah is the theory of social change. This article explains that between da'wah and the theory of social change is a necessity to achieve the goal of changing the condition of a society that is the object of da'wah. Da'wah as an activity of an individual or group of people integrated in a series of Islamic religious doctrines-material activities, needs to touch pure sciences (pure sciences) as the basis for laying various approaches, strategies or methods, and other elements of da'wah.